2022
DOI: 10.1007/s13296-022-00628-9
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of CFST Stub Columns Subjected to Pure Compression

Abstract: Application of concrete-filled steel tubes (CFST) is becoming increasingly prominent in the civil engineering practice. However, the interaction of cross-sectional elements in CFST columns raises a number of questions, which have to be investigated in detail to improve design background and analytical resistance formulae. The aim of the current paper is to examine the structural behaviour of innovative concrete-filled steel tubes using different structural steel grades (S355, S500 and S960) and concrete classe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…The concrete core confinement effect-related research can be found in [18,19,[31][32][33][34]. During the axial load, the inner concrete core gets strengthened by an outer steel profile that affects the bearing capacity of a composite column.…”
Section: Introductionmentioning
confidence: 99%
“…The concrete core confinement effect-related research can be found in [18,19,[31][32][33][34]. During the axial load, the inner concrete core gets strengthened by an outer steel profile that affects the bearing capacity of a composite column.…”
Section: Introductionmentioning
confidence: 99%
“…A concrete-filled steel tube (CFST) is a new type of bearing structure made of a steel tube with concrete [ 11 , 12 ]. Under external load, the deformation of the core concrete is constrained by the steel tube, which can improve the deformability and compressive strength of the concrete.…”
Section: Introductionmentioning
confidence: 99%